Study of the Phase Composition and Structure of the Nanodispersed Al–O Powder Produced by a Plasmodynamic Method - Sivkov A. A. Aleksandr Anatolyevich; Ivashutenko A. S. Alexander Sergeevich; Rakhmatullin I. A. Ilyas Aminovich; Shanenkova Yu. L. Yuliya Leonidovna; Zimmermann A. I. Aleksandr Igorevich (2018, 2018)
Title screen